Contemporary Approaches to Qur'anic Hermeneutics - Sanusi Lafiagi Haruna (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
The problem in this study focuses on the significant changes in Qur'ānic hermeneutics in the modern era, where traditional approaches are often considered inadequate in addressing contemporary issues. This discrepancy creates a need for a more contextualized and inclusive approach to interpretation. This study aims to analyze the transformation of Qur'ānic hermeneutics and offer a more contextual approach without ignoring traditional values. The research used a descriptive qualitative method with a literature review design. The research subjects comprised 15 Muslim scholars and scholars involved in contemporary Qur'anic interpretation. Data were collected through document analysis and in-depth interviews, using an interview guide as an instrument. Data analysis was conducted through content and thematic analysis approaches. The results showed that the contemporary hermeneutic approach is more adaptive to modern social and cultural changes, enriching a more inclusive and contextual interpretation methodology. This study concludes that the transformation of Qur'anic hermeneutics offers interpretations more relevant to the challenges of the times. The implication of this research shows the need for a flexible hermeneutical method to support Muslims' understanding in the modern context.